Penyuluhan Ibu-Ibu PKK/Dawis Dan Guru SMA/SMK “The Miracle Of Antioxidant Therapy For The Degenerative Disease Prevention” - Metrikana Novembrina; Nurista Dida Ayuningtyas; Ferika Indrasari; Sandy Mahesa (Universitas Pahlawan Tuanku Tambusai, 2022)
Oxidative stress plays an important role in the pathophysiology of the aging process and various degenerative diseases. Antioxidants are needed by the body to overcome and prevent oxidative stress. Plants native to Indonesia contain lots of antioxidants. The purpose of providing information or knowledge to PKK/Dawis mothers and SMA/SMK teachers about the efficacy of antioxidant therapy in preventing degenerative diseases. The method used is interactive online discussion. The 25 participants were first given a questionnaire to measure the level of participants' knowledge about the efficacy of antioxidants in the prevention of degenerative diseases. After that, the participants were given material about the efficacy of antioxidants in preventing degenerative diseases. After the activity of delivering the material, the participants were again given a questionnaire to measure the level of understanding related to the material that had been delivered. The results of the implementation of the activities and the results of the questionnaire based on the test. The results of the Mann-Whitney test showed that there was an average difference before and after participating in the training.